2013
DOI: 10.1158/1078-0432.ccr-13-0107
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in Combination with Oxaliplatin, Leucovorin, and Fluorouracil (Modified FOLFOX6) as First-line Treatment of Metastatic Colorectal Cancer: The RESPECT Trial

Abstract: Purpose: This randomized, double-blind, placebo-controlled, phase IIb study evaluated adding sorafenib to first-line modified FOLFOX6 (mFOLFOX6) for metastatic colorectal cancer (mCRC).Experimental Results: Of 198 patients randomized, median PFS for sorafenib plus mFOLFOX6 was 9.1 months versus 8.7 months for placebo plus mFOLFOX6 (HR ¼ 0.88; 95% CI, 0.64-1.23; P ¼ 0.46). There was no difference between treatment arms for overall survival. Subgroup analyses of PFS and overall survival showed no difference betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…This study did not find a PFS benefit with the combination therapy. KRAS and BRAF status did not change this result [53].…”
Section: The Improvement Of Previous Treatmentsmentioning
confidence: 82%
See 1 more Smart Citation
“…This study did not find a PFS benefit with the combination therapy. KRAS and BRAF status did not change this result [53].…”
Section: The Improvement Of Previous Treatmentsmentioning
confidence: 82%
“…In this Asiatic study, lapatinib has been evaluated in combination with paclitaxel versus paclitaxel alone in pretreated HER2 amplified aGCs. OS improvement was not statistically significant in the intention-to-treat population (11.0 vs 8.9 months; HR: 0.84; p = 0.2088) Sorafenib [53] VEGFR Tivozanib [54] Gastric cancer HER2 Lapatinib [66,67] EGFR Erlotinib [61,62] Gefitinib c-MET Foretinib [86] Rilotumumab [87,93] Onartuzumab [88] Hepatocellular carcinoma VEGFR, BRAF, KIT, RET, PDGFR Sunitinib Linifanib [55,56] FGFR Brivanib [57,58] EGFR Erlotinib [59] mTOR Temsirolimus [60] c-MET Foretinib [82] Tivantinib [83] Cabozantinib [84] MEK Selumetinib [89,90] IGF/IGFR Cixutumumab [91] The role of targeted therapy for GI tumors Review informahealthcare.com while in the Chinese subgroup of HER2-positive patients, this improvement was higher [67]. In many Phase II trials, the association of cetuximab with chemotherapy has been shown to have some efficacy [68,69] and based on the increase of RR in previous studies, Richards et al evaluated in a Phase II trial the combination of cetuximab and chemotherapy with docetaxel plus oxaliplatin (DOCOX) versus chemotherapy alone in patients affected with metastatic gastric and GEJ adenocarcinoma.…”
Section: The Improvement Of Previous Treatmentsmentioning
confidence: 86%
“…Unfortunately, both failed to improve prognosis in phase III randomized trials, even if sorafenib still maintains promise for pretreated KRAS mutant patients. [16][17][18] Other antiangiogenic molecules able to target multiple pathways are under investigation. Among these, nintedanib (BIBF 1120), a multi target TKI able to efficiently block VEGFR, FGFR and PDGFR, is one of the most promising, as it has already shown to improve survival in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In phase 2, an encouraging response rate of 64.9% was noted with a PFS of 3.7 mo and a median OS of 8 mo [73] . However, in a subsequent phase Ⅱb study of 198 treatment naive mCRC patient, the combination of sorafenib and mFOLFOX4 was shown to offer no PFS or OS advantage over placebo (Table 3) [74] .…”
Section: Other Anti-angiogenic Agentsmentioning
confidence: 99%